A new small molecule DHODH-inhibitor [KIO-100 (PP-001)] targeting activated T cells for intraocular treatment of uveitis — A phase I clinical trial - Thurau, Stephan; Deuter, Christoph M. E.; Heiligenhaus, Arnd; Pleyer, Uwe; Van Calster, Joachim; Barisani-Asenbauer, Talin; Obermayr, Franz; Sperl, Stefan; Seda-Zehetner, Romana; Wildner, Gerhild (Frontiers in Medicine, 2022)
Uveitis is a T cell-mediated, intraocular inflammatory disease and one of the main causes of blindness in industrialized countries. There is a high unmet need for new immunomodulatory, steroid-sparing therapies, since only ciclosporin A and a single TNF-γ-blocker are approved for noninfectious uveitis. A new small molecule inhibitor of dihydroorotate dehydrogenase (DHODH), an enzyme pivotal for de novo synthesis of pyrimidines, has a high potency for suppressing T and B cells and has already proven highly effective for treating uveitis in experimental rat models. Systemic and intraocular application of KIO-100 (PP-001) (previously called PP-001, now KIO-100) could efficiently suppress rat uveitis in a preventive as well as therapeutic mode. Here we describe the outcome of the first clinical phase 1 trial comparing three different doses of a single intraocular injection of KIO-100 (PP- 001) in patients with noninfectious posterior segment uveitis (ClinicalTrials.gov Identifier: NCT03634475). No toxic side effects on intraocular tissues or other adverse events were observed, while intraocular inflammation decreased, and visual acuity significantly improved. Macular edema, a sight-threatening complication in uveitis, showed regression two weeks after intraocular KIO-100 (PP- 001) injection in some patients, indicating that this novel small molecule has a high potential as a new intraocular therapy for uveitis.